Evaluation of a convenient vaccination schedule against hepatitis B in HIV-patients with undetectable HIV viral load. Issue 12 (14th March 2018) - Kourkounti, Sofia; Retsas, Theodoros; Paparizos, Vassilios; Tsimpidakis, Antonios; Kapsimali, Violetta; Rigopoulos, Dimitrios
Highlights: Immune response to 3 doses HBVaxPro 40 mg (0, 1 and 6 months) was 79%. HBVaxPRO caused higher antibody titers compared to standard regimen. 60% of HBVaxPro responders maintained protective antibody titers at month 24. Higher response to HBVaxPro occurred among younger people. The higher dose of HBVaxPro may be a better alternative. Abstract: Vaccination against hepatitis B virus (HBV) is recommended for all HIV-positive individuals but the standard schedule is not satisfactory. High or more doses have also been studied with variable results. We compared a vaccination schedule with a higher dose but fewer shots to the standard scheme (HBVaxPro 40 μg versus Engerix 20 μg at 0, 1, and 6 months). Of the 63 patients vaccinated with HBVaxPro 79%, 65% and 47% seroconverted at month 1, 12 and 24 after vaccination, respectively. A total of 137 patients received Engerix and showed lower response rates (68%, 53% and 38%, respectively). Anti-HBs titers in the Engerix group were also lower with a statistically significant difference. In patients younger than 55 years HBVaxPro was 3 times more likely to provoke a response compared with Engerix (OR = 3, p = 0.006). In conclusion, HBVaxPro 40 μg at 3 doses could be proposed as a more robust and acceptable alternative.